SIPLah, Sistem Pengadaan Barang Dan Jasa Berbasis Elektronik Di Sekolah Dasar Kecamatan Bukit Bestari - MUHAMMAD, ADJI SURADJI; Pamilia, Syantika Cahya; Okparizan, Okparizan (Jurnal Pendidikan Kewarganegaraan Undiksha, 2024)
The procurement policy via SIPLah was adopted by the Ministry of Education and Culture to streamline school procurement online using BOS funds and to strengthen accountability in fund utilization. This study evaluates the implementation of SIPLah in primary schools in Bukit Bestari Subdistrict, Tanjungpinang City, and describes implementation barriers. Data were collected through observation, interviews, and documentation, then analyzed through data reduction, display, and conclusion drawing, guided by Grindle’s implementation framework. Findings show that, of nine indicators, eight operate optimally—namely the interests affected by the policy, benefits received, locus of decision making, program implementers, mobilized resources, actors’ power/interests/strategies, institutional and ruling-regime characteristics, and levels of compliance and responsiveness—while the degree of change sought remains suboptimal. Key obstacles include: (1) incomplete local availability of goods/services in Tanjungpinang; (2) schools bearing shipping costs when vendors are located outside the city; (3) frequent absence of required items on the platform, necessitating prior vendor confirmation and product uploading; (4) SIPLah procurement perceived as slower than conventional methods; and (5) technical difficulties in handling taxes during transactions. These findings suggest the need to expand the SIPLah catalogue and onboard local vendors, introduce shipping subsidies or standardized rates, simplify workflows and service-level agreements, and provide taxation support alongside electronic document integration, so that the intended change greater efficiency, transparency, and ease of procurement using BOS funds can be achieved more evenly.